2020
DOI: 10.17159/2078-5151/2020/v58n1a2814
|View full text |Cite
|
Sign up to set email alerts
|

Age is a predictor of significant endoscopic findings in dyspepsia patients in South Africa

Abstract: Background: Dyspepsia is the commonest indication for endoscopy. Current American guidelines recommend that all dyspepsia patients ≥ 60 years undergo endoscopy to exclude significant pathology. The use of this age cutoff has never been analysed in South Africa. We aimed to compare different age cutoffs as predictors of significant endoscopic findings in patients with a primary diagnosis of dyspepsia. Methods: A retrospective chart review of 1 000 consecutive endoscopies done at Madadeni Provincial Hospital, Kw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In both univariate and multivariate analyses, UGIB was found to be strongly correlated to SEFs. Supporting our finding, a retrospective study reviewing 1000 consecutive endoscopies performed at rural South African hospitals showed that UGIB was similarly the most prevalent alarm feature[ 9 ], and it showed a statistically significant correlation with major endoscopic findings.…”
Section: Discussionsupporting
confidence: 83%
“…In both univariate and multivariate analyses, UGIB was found to be strongly correlated to SEFs. Supporting our finding, a retrospective study reviewing 1000 consecutive endoscopies performed at rural South African hospitals showed that UGIB was similarly the most prevalent alarm feature[ 9 ], and it showed a statistically significant correlation with major endoscopic findings.…”
Section: Discussionsupporting
confidence: 83%
“…32 However, a combination of a PPI and prokinetic can help reduce both EPS and PDS symptoms in patients with FD. 33 It is noteworthy to understand that the majority of the clinicians in this survey reported itopride to be the optimum prokinetic for treatment of patients with FD considering that the proportion of patients who were prescribed itopride was higher than those prescribed acotiamide and domperidone. These practices are consistent with findings from a study by Takeshi et al wherein 97.3% of patients with PDS were found to benefit from itopride.…”
Section: Discussionmentioning
confidence: 86%
“…In this study,71% patients have normal endoscopic findings and 29% patients have abnormal endoscopic findings where majority of the patient were 51 -70 years of age.We observed thatpatient below age of 30 years presented with dyspepsia were normal andendoscopy not routinely needed for further management. A study conducted in south Africa suggested that,Patients > 60 years with dyspepsia symptoms should undergo a routine endoscopy 12 .…”
Section: Discussionmentioning
confidence: 99%